Electronic Properties and CO2-Selective Adsorption of (NiB)n (n = 1~10) Clusters: A Density Functional Theory Study - Meiling Hou; Xing Zhou; Chao Fu; Tingting Nie; Yu Meng (Molecules, 2023)
In this study, we investigated the electronic properties and selective adsorption for CO2 of nickel boride clusters (NiB)n, (n = 1~10) using the first principles method. We optimized the structures of the clusters and analyzed their stability based on binding energy per atom. It was observed that (NiB)n clusters adopt 3D geometries from n = 4, which were more stable compared to the plane clusters. The vertical electron affinity, vertical ionization energy, chemical potential, and highest occupied molecular orbital (HOMO)–lowest unoccupied molecular orbital (LUMO) gap were calculated. Our results revealed that (NiB)6 and (NiB)10, with high chemical potential, exhibit a higher affinity for CO2 adsorption due to a charge delivery channel that forms along the Ni→B→CO2 path. Notably, (NiB)10 demonstrated a more practical CO2 desorption temperature, as well as a broader window for the selective adsorption of CO2 over N2. The density of states analysis showed that the enhanced CO2 adsorption on (NiB)10 can be attributed to the synergistic effect between Ni and B, which provides more active sites for CO2 adsorption and promotes the electron transfer from the surface to the CO2 molecule. Our theoretical results imply that (NiB)10 should be a promising candidate for CO2 capture.